„Problemy Kościoła obecne w kanonach dyscyplinarnych Soboru Nicejskiego I” – zjazd Sekcji Patrystycznej (Obra, 15-17.09.2025) - Pakowski, Grzegorz (Vox Patrum, 2025)
Report from the annual meeting of the Polish Patristic Section with the conference entitled: “The problems of the Church present in the disciplinary canons of the First Council of Nicaea” that took place in Obra, Poland on 15-17.09.2025.